FRI0019 Divergent Effects of Free Fatty Acids on Cells of Bone Metabolism. (15th July 2016) - Frommer, K.; Schäffler, A.; Lange, U.; Rehart, S.; Steinmeyer, J.; Rickert, M.; Müller-Ladner, U.; Neumann, E.
Abstract : Background: Adipose tissue secretes numerous bioactive substances, which contribute to inflammation. Chronically elevated free fatty acid (FFA) levels are known to be associated with numerous inflammatory cardiovascular and metabolic diseases such as atherosclerosis, coronary heart diseases and type 2 diabetes. Conversely, inflammation can contribute to bone loss. FFA may therefore be a contributing factor in bone loss in osteoarthritis (OA) and/or rheumatoid arthritis (RA). Interestingly, obesity is associated with a higher risk of OA also in non-weight bearing joints and increased amounts of visceral fat are associated with lower bone density. Objectives: To test the hypothesis that FFA affect cells of bone metabolism in the context of rheumatic diseases in a way that promotes bone loss. Methods: Primary osteoblasts (OB) were isolated from cancellous bone of OA and RA patients undergoing knee joint surgery. Osteoclasts (OC) were differentiated from peripheral blood mononuclear cells (PBMC). OB and OC were stimulated with the saturated FFA palmitic acid (PA) and the unsaturated FFA linoleic acid (LA). Immunoassays were used to quantify protein secretion. mRNA expression levels were quantified by real-time PCR. Mineralization activity was quantified using Alizarin Red S staining, differentiated OC were quantified by counting TRAP-positive multinuclear cells. Toll-like receptor (TLR) 4 and TLR2 were blocked by neutralizing antibodies. Results: Both PA and LA increased the secretion of the proinflammatory cytokine IL-6 (up to 9-fold) and the chemokines IL-8 (up to 221-fold), GRO-a (from below detection level to detectable levels) and MCP-1 (up to 16-fold). The degree of response was highly dependent upon the patient. RANKL as well as OPG, important regulators of osteoclastogenesis and OC activity, remained unaffected by FFA on protein and mRNA level. OB activity markers alkaline phosphatase (ALP) and collagen type I as well as markers of OB differentiation (e.g. osteocalcin) also remained unchanged after FFA stimulation. PA-induced IL-8 secretion by OB could be significantly reduced by TLR4 blockade (by 93%), while blocking TLR2 had no effect. Upon stimulation with PA and LA, secretion of IL-8 by RA OC was increased and MMP-9 reduced and the number of TRAP positive multinuclear cells decreased (by around 50%). Further markers of osteoclast activity (CLCN7, CTSK, TCIRG) remained unchanged. Conclusions: The effect of FFA on cells of bone metabolism appears to be divergent: While FFA promote a pro-inflammatory phenotype in OB and may thus indirectly contribute to bone loss, the effects on OC mainly suggest an inhibitory effect on bone resorption. Disclosure of Interest: None declared